Museum communication: the current state of research and challenges for linguistics - Czachur, Waldemar; Mikołajczyk, Beata; Opiłowski, Roman (Stylistyka, 2023)
This paper deals with communication processes taking place in the museum, collectively referred to as museum communication, from the point of view of contemporary linguistics. Based on previous research, museum communication is defined as a kind of interplay of multiple communicative practices multimodally organised within a museum and activated in communication with the museum’s external partners. Linguistics has so far looked at museum communication mainly in terms of language use, including other semiotic systems, with particular attention to the related communicative strategies and practices, genres of texts, and their functions, both in internal and external communication. However, the paper argues that the scope of tools used to study museum communication should be broadened. The key determinants of museum communication include multimodality, multisensoriality, hybridity, and digitality. The paper provides a review of linguistic models of analysis with a variety of tools and solutions that have been developed for the study of multimodal texts with similar attributes in different communicative fields. The review is then used to develop a catalogue of linguistic analytical categories that can be applied to detailed analyses of particular aspects of museum communication.